A Study Prevalence And Associated Factors Of Pshycological Stress Among Early Childhood In Kuantan, Pahang - Nurul Izzah A’tirah, Rusni (2025)
Background: Early childhood teachers’ psychological stress has a big impact on long-term mental and physical health. Designing successful therapies requires an understanding of their prevalence and associated factors. The purpose of this study is to determine the prevalence of psychological stress among early childhood teachers in Kuantan, Pahang, as well as personal traits, working environment, personal factors and organizational factors are linked to it. Method: A representative sample of early childhood teachers in Kuantan, Pahang, participated in a cross-sectional study. Validated psychological stress questions were used to gather data on sociodemographic, psychological stress symptoms and possible stressors such as student misbehaviour, relationships with colleagues and school, and other variables. To find meaningful correlations, statistical analysis was done. Findings: Of the teachers, 45% have depression, 100% having anxiety and 55% having stress. Personal traits (p=0.001), working environments (p=0.003), and organizational factors (p=0.01) were important variables that were substantially linked to stress. Psychosocial programs and protective variables were found. Conclusion: The results show that psychological stress is quite common among early childhood teachers in Kuantan, Pahang and emphasise the significance of focused interventions to address risk factors that can be changed. It is advised that parents, teachers and school administrators work together to help teachers become more resilient and reduce stress.